Interrogating the adoption of the updated primary school curriculum in Zimbabwe: Implications for staff development and quality education - Douglas Gasva; Rodney Joe Phiri (Association for Scientific Computing Electrical and Engineering(ASCEE), 2020)
This study aims to interrogate the adoption of the updated primary school curriculum in Zimbabwe to determine its implications for staff development and the delivery of quality education. The study adopted the qualitative paradigm and utilized the case study design delimited to five schools in the Hwange District of Matabeleland North Province in Zimbabwe. Purposive sampling method was used to identify participants, while Focus Group Discussions (FGDs) and Interviews were used as the research techniques meant for data generation. Consistent with phenomenological inquiries, data were analyzed through interpretive phenomenological analysis (IPA), while findings were presented in summarised prose form. The key findings of the study were that the adoption of the updated curriculum had necessitated the need for teachers' professional development to equip them with the necessary knowledge and pedagogic skills which they generally lacked considering that the teachers did not study new learning areas of the curriculum during their initial teacher training. Besides, there was a lack of knowledgeable and competent facilitators in the updated curriculum's new learning areas, hence needing staff development. The researchers concluded that the adoption of the updated primary school curriculum had been a major spur for staff development for teachers; hence, it brought a new trajectory where teachers' continuous professional development is necessary rather than an option if quality education is to be realized. The researchers, therefore, recommended that the Ministry of Primary and Secondary Education (MoPSE) should step up support for the professional development of teachers considering that the adoption of the updated curriculum has implications for the delivery of quality education in Zimbabwe